Hybrid Arch Repair with Supra-Aortic Debranching and Using Castor Stent-Graft - Gao, Xijie; Liu, Guohong; Lu, Jun; Zhao, Jianbo (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Background The management of aortic lesions involving the aortic arch in patients who cannot tolerate thoracotomy is a challenge.Case Description A 32-year-old woman who underwent a giant aneurysm at the proximal end of the descending aorta with significant vascular wall calcification. The patient underwent Castor single-branched stent-grafting in the brachiocephalic trunk combined with surgical supra-aortic debranching, which avoided surgical aortic arch replacement and stent fenestration.reopening. The patient was followed up for 9 months, and surgery-related complications were not observed.Conclusion Hybrid arch repair with supra-aortic debranching and using Castor single-branched stent can be used to treat aortic lesions involving the aortic arch.
Keywords: aortic disease; aneurysm; endovascular procedures/stents; except PCI